Pengaruh Intellectual Capital, Enterprise Risk Management dan Kebijakan Dividen terhadap Nilai Perusahaan - Lindawati, Lindawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In today's competitive and dynamic business environment, intangible assets such as intellectual capital and effective risk management have become essential in driving firm value, particularly in the property and real estate sector. Companies are expected not only to manage physical assets but also to optimize knowledge, innovation, and strategic financial policies. This study aims to analyze and provide empirical evidence on the influence of intellectual capital, enterprise risk management (ERM), and dividend policy on firm value. The research was conducted on property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. A purposive sampling technique was applied, resulting in a sample of 7 companies over 5 years, totaling 35 data observations. The data were analyzed using panel data regression with EViews version 9. The results show that simultaneously, intellectual capital, ERM, and dividend policy have a significant impact on firm value. However, when tested partially, only intellectual capital has a significant positive influence, while ERM and dividend policy do not significantly affect firm value. These findings suggest that firms should prioritize the development of intellectual capital as a key driver of value creation, while also revisiting their risk management and dividend distribution strategies.